Opening Up Fieldwork with Ethnographic Poetry - Kusserow, Adrie Suzanne (Anthropologica, 2020)
<span style="color: #000000; font-family: 'Open Sans', Arial, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Four ethnographic poems are used to explore, elucidate and complexify four ethnographic encounters in the field. Each poem is accompanied by a brief explanation as to the ethnographic context in which the poem was written, as well as the reasons why an ethnographic poem was chosen as a tool to illuminate, complexify and do justice to these varying fieldwork experiences. The strengths of ethnographic poetry as a rigorous and subtle tool for cross-cultural understanding is addressed.